A cross-cultural perspective on creative leadership and change management: a case study of the influence of Barack Obama's early years. (2016) - Rich, Grant J.
Though his public life as the 44th president of the USA is well known, this article examines the early life of Barack Obama as a case study with implications for better understanding the influence of early multicultural experience on leadership and change management. Using a strengths-based positive psychology perspective, Obama's development will be explored through the use of primary sources such as his books (Obama, 2004, 2006), existing scholarly analysis of his childhood and youth (e.g., Gielen, 2013; Sharma, 2011; Sharma and Gielen, 2014), and information from various news media.